2007
DOI: 10.1002/jts.20226
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation and pain perception: An experimental investigation

Abstract: Dissociative symptoms and abnormalities in pain perception have been associated with a range of disorders. The authors tested whether experimentally induced increases in state dissociation would cause an analgesic response. Participants (N = 120) were randomized to a dissociation induction condition via audiophotic stimulation or a credible control condition and were compared on pre‐ and postchanges in subjective pain and immersion time in response to a standard cold pressor test. Unexpectedly, the dissociatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…The current and previous findings (Chou et al, 2014;Holmes et al, 2004Holmes et al, , 2006 suggest that aversiveaudiovisual stimulation, i.e., mere audiovisual witnessing a traumatic event without being personally involved, might already suffice to evoke dissociation. In line with evolutionary models proposing that encountering a direct physical threat to one's life might be an important factor contributing to the rise of dissociation (Schauer & Elbert, 2010), painful-stimulation also evoked dissociation in our and previous studies (Giesbrecht et al, 2008;Gómez-Pérez et al, 2013;Horowitz & Telch, 2007). This is in line with the idea that pain constitutes a signal of tissue damage which might limit the fight-or-flight capacity and thereby promote dissociation as an adaptive response.…”
Section: Trauma Features Eliciting Dissociationsupporting
confidence: 92%
See 1 more Smart Citation
“…The current and previous findings (Chou et al, 2014;Holmes et al, 2004Holmes et al, , 2006 suggest that aversiveaudiovisual stimulation, i.e., mere audiovisual witnessing a traumatic event without being personally involved, might already suffice to evoke dissociation. In line with evolutionary models proposing that encountering a direct physical threat to one's life might be an important factor contributing to the rise of dissociation (Schauer & Elbert, 2010), painful-stimulation also evoked dissociation in our and previous studies (Giesbrecht et al, 2008;Gómez-Pérez et al, 2013;Horowitz & Telch, 2007). This is in line with the idea that pain constitutes a signal of tissue damage which might limit the fight-or-flight capacity and thereby promote dissociation as an adaptive response.…”
Section: Trauma Features Eliciting Dissociationsupporting
confidence: 92%
“…Other studies had healthy participants hold their arm into pain-eliciting ice water. Participants reported higher dissociation after the task compared to a pre-task baseline (Giesbrecht et al, 2008;Gómez-Pérez et al, 2013;Horowitz & Telch, 2007), suggesting that painful stimulation (without simultaneously witnessing aversive-audiovisual material) can also evoke dissociation. However, so far analogue studies have lacked control conditions ensuring that dissociation is driven by the aversive-audiovisual or painful stimulation and not by general task, time, or demand effects.…”
Section: Trauma Features Eliciting Dissociationmentioning
confidence: 96%
“…In highly dissociative states, pain sensations may be perceived as sensory fragments, which are difficult to comprehend (van der Kolk & Fisler, 1995). Nevertheless, findings reveal that induced dissociation is linked with small, yet significant increases in sensitivity to pain (Horowitz & Telch, 2007). In parallel, the current findings indicate that children experience intensive pain, which, although highly intense, is also difficult to locate.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that dissociation may have played a role in the increased tolerance for acute pain. Other adult studies utilizing chronic pain samples (Duckworth et al, 2000) and laboratory settings (Horowitz & Telch, 2007) have suggested a positive association between dissociation and heightened pain perception. The inconsistent findings highlight the complexity of this issue and suggest that further exploration of the association between trauma, dissociation, and pain in both pediatric and adult samples is necessary.…”
Section: Downloaded By [University Of Glasgow] At 16:19 20 December 2014mentioning
confidence: 98%